Divulgação científica sobre a química verde em vídeo: reflexões dialógicas - Rúbia Lúcia Pereira (2020)
The dynamics of the classroom in High School classes may be more efficient with the use of multisemiotic (various signs) and multimedia resources. Inspired by Bakhtin’s dialogism ideas, we consider that understanding for the construction of knowledge starts from the assimilation and appropriation of the many voices shared in the school environment and in society. The search for new ways to teach Green Chemistry in High School resulted in the idea of using a Science Communication video with an environmental chemistry theme that could be integrated to classroom activities that aimed to teach regular curricular content. The educational resource described in this work has two parts. The first one is a short video (3 minutes) that shows the existence of an environmental problem and the proposed solution by the brazilian researchers of the National Institute of Science and Technology - Midas project (INCT /Midas). The video´s format and content was designed to work as a Science Communication piece. The second part of the educational resource is a didactic sequence designed to teach Solutions and concentration units content for High School students, that was based on and used the Science Communication video from the first part. The didactic sequence was used in two classes of High School first year students. The results from the analysis of the students' answers in the activities were used to reformulate the didactic sequence. Fifteen questions from the didactic sequence were selected and the ATD methodology - discursive textual analysis - was used in the students' productions. The results of the analysis of the students' responses in the activities showed their ideas about understanding the concept in several aspects: phenomenological, representational and theoretical in the study of solutions. These results contributed to reformulate the didactic sequence.